Risk of Environmental Factors and Efforts to Eliminate Mosquito Nest with Dengue Fever in The Working Area of The Kamonji Health Center - Rau, Muhammad Jusman; Banilai, Puti Andalusia Sarigando (Tadulako University, 2020)
Dengue High Fever (DHF) is a contagious health problem in tropical areas like Indonesia. Palu city has the highest cases of DHF that is 600 cases (Incidence Rate 166,2/100.000 population) and there are 9 people died. Incidence of DHF in the working area of Kamonji public health center are 106 cases. Factors that cause DHF in this working area are environment and behavior of community. The study aimsis determine risk factors of environment and eradication of mosquito nests efforts in the working area of Kamonji Public Health Center. This type of research is case-control approach and the sample taken from Total Sampling technique which amounts to 86 respondents with a ratio 1:1. Data analysis was performed using univariate and bivariate at 95% confidence level (α=0,05) which shows that precenses of larvae in breeding place (OR=0,334) and drain water containers (OR=0,237) are protective factors. Another result shows that presences of mosquito in resting place (OR=3,654), close water containers (OR=4,032), the use of abate (OR=3,048) and the use of anti-mosquito drugs (OR=4,909) are risk factors of incidence of DHF in working area of Kamonji public health center. The efforts to prevent incidence of DHF is implement eradication of mosquito nest so that the environment around the house still clean and has no chance for become breeding place of Aedes aegypti.